Hybrid-integrated version of solid-state components for terahertz frequency region - Zorenko, O.V.; Bychok, A.V.; Kryts’ka, T.V.; Kudryk, Ya.Ya.; Shynkarenko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
We present the results of development of key components for THz devices
obtained using mathematical modeling of detector sections, radiation source and
subharmonic mixers. Schottky barrier diodes with different parameters served as
nonlinear elements of the above facilities.